Aesthetic Surgery Complications: Medical Legal Responsibilities and Health Insurance Claims - Faisal Lutfi; Marice Simarmata; T Riza Zarzani (CV. Era Digital Nusantara, 2026)
Aesthetic surgery, as an elective medical procedure, has its own legal complexities, particularly when complications occur or results do not meet patient expectations. This study aims to analyze the regulations and limitations of physicians' legal liability in aesthetic surgery, as well as examine the role of informed consent and therapeutic agreements in legal liability. The research method uses a qualitative approach through a literature review of laws and regulations, legal doctrine, court decisions, and related literature. The results of the study indicate that complications are not necessarily categorized as malpractice if the procedure meets professional and service standards. Legal liability only arises if there is a breach of obligation, professional negligence, or failure to comply with the standard of care that causes harm. Informed consent and therapeutic agreements play a strategic role as the basis for legal relationships, protecting patient rights, and limiting physicians' liability for claims of dissatisfaction with results. It is concluded that the implementation of professional standards and proper documentation of consent are key to addressing the legal risks of aesthetic surgery.